NAPB – a novel SNARE‐associated protein for early‐onset epileptic encephalopathy. Issue 2 (28th August 2015) - Conroy, J.; Allen, N.M.; Gorman, K. M.; Shahwan, A.; Ennis, S.; Lynch, S.A.; King, M.D.
ABSTRACT: Next‐generation sequencing has accelerated the identification of disease genes in many rare genetic disorders including early‐onset epileptic encephalopathies (EOEEs). While many of these disorders are caused by neuronal channelopathies, the role of synaptic and related neuronal proteins are increasingly being described. Here, we report a 6‐year‐old girl with unexplained EOEE characterized by multifocal seizures and profound global developmental delay. Recessive inheritance was considered due to parental consanguinity and Irish Traveller descent. Exome sequencing was performed. Variant prioritization identified a homozygous nonsense variant in the N‐ethylmaleimide‐sensitive factor attachment protein, beta ( NAPB ) gene resulting in a premature stop codon and 46% loss of the protein. NAPB plays a role in soluble N‐ethylmaleimide‐sensitive fusion attachment protein receptor (SNARE)‐complex dissociation and recycling (synaptic vesicle docking). Knockout mouse models of the murine ortholog Napb have been previously reported. These mice develop recurrent post‐natal epileptic seizures in the absence of structural brain changes. The identification of a disease‐causing variant in NAPB further recognizes the importance of the SNARE complex in the development of epilepsy and suggests that this gene should be considered in patients with unexplained EOEE.